2020
DOI: 10.2337/db19-1238
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Causes of Severe Childhood Obesity: A Remarkably High Prevalence in an Inbred Population of Pakistan

Abstract: Monogenic forms of obesity have been identified in ≤10% of severely obese European patients. However, the overall spectrum of deleterious variants (point mutations and structural variants) responsible for childhood severe obesity remains elusive. In this study, we genetically screened 225 severely obese children from consanguineous Pakistani families through a combination of techniques, including an in-house–developed augmented whole-exome sequencing method (CoDE-seq) that enables simultaneous detection of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…Additionally, as monogenic obesity often demonstrates a recessive inheritance pattern 31 , consanguinity in populations has further increased the chance of identifying mutations, owing to greater chances of homozygosity of deleterious mutations 32 . For example, studies have reported that mutations in the genes encoding leptin, LEPR and MC4R explain 30% of cases of severe obesity in children from a consanguineous Pakistani population 33 , and single-gene defects more broadly account for nearly 50% 34 .…”
Section: ();mentioning
confidence: 99%
“…Additionally, as monogenic obesity often demonstrates a recessive inheritance pattern 31 , consanguinity in populations has further increased the chance of identifying mutations, owing to greater chances of homozygosity of deleterious mutations 32 . For example, studies have reported that mutations in the genes encoding leptin, LEPR and MC4R explain 30% of cases of severe obesity in children from a consanguineous Pakistani population 33 , and single-gene defects more broadly account for nearly 50% 34 .…”
Section: ();mentioning
confidence: 99%
“…However, in the aggregate, they are responsible for 5% to 10% of obesity cases in populations of European descent, but it could be higher depending on the population and the extent of the diagnosis effort (69). The prevalence of severe obesity cases can be markedly higher in inbred populations as shown in a recent study of consanguineous families from Pakistan in which 59% of cases in a cohort of 225 children with severe obesity were shown to have a likely genetic cause (70). It has been estimated that one person in 24,000 of the United States population carries a deficient allele at LEPR , POMC , or PCSK1 (71).…”
Section: Obesity At the Genome Levelmentioning
confidence: 99%
“…In our large cohort of unrelated Pakistani children with severe obesity (named Severe Obesity in Pakistani Population [SOPP] -Children cohort), we previously demonstrated genetic causality in 49% of the cases (10). Importantly, almost half of these monogenic obesity diagnoses were due to pathogenic, homozygous mutations in the LEP (encoding leptin).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, almost half of these monogenic obesity diagnoses were due to pathogenic, homozygous mutations in the LEP (encoding leptin). The other pathogenic mutations or copy number variants (CNV) were found in LEPR, MC4R, ADCY3, or in Bardet-Biedel, Alström, and Prader-Willi syndrome regions (10). The exceptionally high prevalence of monogenic obesity in Pakistani children prompted us to assess the prevalence of monogenic obesity in a new cohort of severely obese, young adults from Pakistan (SOPP -Young Adults).…”
Section: Introductionmentioning
confidence: 99%